Use of the freshwater crab Trichodactylus fluviatilis to biomonitoring Al and Mn contamination in river water. - Chagas, Graziela C.; Brossi-Garcia, Ana Luiza; Menegario, Amauri Antonio; Franchi, Mariana; Simoes Piao, Antonio Carlos; Silvio Govone, Jose (My University, 2009)
Determinations of Al and Mn concentrations in the tissues (gills, hepatopancreas and muscle) of the freshwater crab Trichodactylus fluviatilis and water samples, both collected from sites on tributaries of the Corumbatai River (São Paulo, Brazil) were performed. The Bioaccumulation Factor (BAF), calculated for different sites with respect to the water concentration, ranged from 173-555 for Al and from 636 - 921 for Mn. Dissolved concentrations of Al and Mn in water samples (collected in different sites) were related to the accumulation of these metals in crabs, suggesting that T. fluviatilis is good biomonitor for Al and Mn pollution in aquatic ecosystem.